The Effect of Group Counseling Program on 8th Grade Students’ Assertiveness Levels - SEÇER, İsmail (Gaziantep University, 2018)
This study is conducted to determine the effects of group counseling program on elementary school 8th grade students’ assertiveness skills. Study group was formed of 100 students getting educated in Erzurum Kültür Elementary School in 2011-2012 education years. RAE-Rathus Assertiveness Schedule was applied on this group to gather data. 30 students getting lower scores from the inventory have been randomly divided into experimental and control groups. Each group is formed of 15 students. Group counseling program has been carried out for 8 weeks on the experimental group to improve the students’ assertiveness skills. Single-way and two-way analysis of covariance (ANCOVA) has been used in the analysis of the data. The data is analyzed with SPSS 19.00. The results of the study show that assertiveness skills of the students who participate in the group counseling program has increased significantly compared to the control group and to the preexperimental circumstances. Besides, it is determined that the change observed in the experimental group has been occurred separately from the age and socio-economic level variables, and it is determined with the monitoring test applied after four months that this affect is continued. According to this result, it can be said that the applied group counseling program is an effective means to improve the assertiveness skills of elementary school students